Long‐Lived Spin States for Low‐Field Hyperpolarized Gas MRI. Issue 45 (26th September 2014) - Kovtunov, Kirill V.; Truong, Milton L.; Barskiy, Danila A.; Koptyug, Igor V.; Coffey, Aaron M.; Waddell, Kevin W.; Chekmenev, Eduard Y.
Abstract Parahydrogen induced polarization was employed to prepare a relatively long‐lived correlated nuclear spin state between methylene and methyl protons in propane gas. Conventionally, such states are converted into a strong NMR signal enhancement by transferring the reaction product to a high magnetic field in an adiabatic longitudinal transport after dissociation engenders net alignment (ALTADENA) experiment. However, the relaxation time T1 of ∼0.6 s of the resulting hyperpolarized propane is too short for potential biomedical applications. The presented alternative approach employs low‐field MRI to preserve the initial correlated state with a much longer decay time TLLSS=(4.7±0.5) s. While the direct detection at low‐magnetic fields (e.g. 0.0475 T) is challenging, we demonstrate here that spin‐lock induced crossing (SLIC) at this low magnetic field transforms the long‐lived correlated state into an observable nuclear magnetization suitable for MRI with sub‐millimeter and sub‐second spatial and temporal resolution, respectively. Propane is a non‐toxic gas, and therefore, these results potentially enable low‐cost high‐resolution high‐speed MRI of gases for functional imaging of lungs and other applications.